(untitled) - Pilat, Stefan (Bohemica Olomucensia, 2020)
The paper discusses perspectives of further development of the Old Church Slavonic Dictionary and possible problems associated with such processes. The ongoing digitization of the dictionary opens new possibilities for its development, most importantly an equalization of the differences that have arisen among its four parts. It brings also an option to expand the dictionary with other Old Church Slavonic texts and the digitization enables entirely new approach to the Czech Church Slavonic material as a whole.
Keywords: lexicography; digitization; Old Church Slavonic language; Old Church Slavonic texts; Czech recension of the Church Slavonic language